The Educational Video as a Parental Mediation in Regulating Smartphone Use for Early Childhood: A Research and Development Study - Yuniarni, Desni (Universitas Pendidikan Ganesha, 2025)
The rapid increase in smartphone use among young children has raised concerns about its potential impact on early childhood development. This study aimed to develop an educational video as a parental support tool using a Research and Development (R&D) approach guided by the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through structured interviews and standardized questionnaires involving parents of early childhood education (ECE) students. Content validation was conducted by ECE lecturers, while media validation involved experienced ECE teachers. During the analysis phase, parental needs related to content and media format were identified. The design and development phases produced a video based on these needs, followed by expert validation. The implementation phase involved limited testing with parents of children aged 3–6, and evaluation measured content quality, media design, and user responses. Results indicate that the video is pedagogically appropriate, user-friendly, and positively received, enhancing parental understanding and self-efficacy. This study highlights the importance of responsive multimedia tools in supporting digital-age parenting practices.